2014
DOI: 10.1080/08897077.2014.898605
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Withdrawal in Patients with and without Opioid Dependence

Abstract: Background Cannabis use is common among opioid-dependent individuals, but little is known about cannabis withdrawal in this population. Method Thirty inpatients (57% men) completed the Marijuana Quit Questionnaire (MJQQ) after completing acute heroin detoxification treatment in St. Petersburg, Russia. The MJQQ collected data on motivations for quitting, withdrawal symptoms, and coping strategies used to help maintain abstinence during their most “userious” (self-defined) quit attempt made without formal trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“… 63 This may be due to the low doses of rimonabant applied (20 and 40 mg) or the CWS-generating mechanisms that are at least partly independent upon CB1 receptors. 49 , 50 Cannabis users with opioid dependence are less likely to experience CWS, 64 which may indicate the contribution of the endogenous opioid system. In a laboratory study, the µ-opioid receptor antagonist naltrexone was recently shown to reduce self-administration of active cannabis and its related subjective positive effects on heavy cannabis users.…”
Section: Human Biological Backgroundmentioning
confidence: 99%
“… 63 This may be due to the low doses of rimonabant applied (20 and 40 mg) or the CWS-generating mechanisms that are at least partly independent upon CB1 receptors. 49 , 50 Cannabis users with opioid dependence are less likely to experience CWS, 64 which may indicate the contribution of the endogenous opioid system. In a laboratory study, the µ-opioid receptor antagonist naltrexone was recently shown to reduce self-administration of active cannabis and its related subjective positive effects on heavy cannabis users.…”
Section: Human Biological Backgroundmentioning
confidence: 99%
“…In contrast, amphetamine and cocaine withdrawal may be milder, and there are few or no pharmacological strategies for these conditions (Kosten & O’Connor, 2003; Srisurapanont, Jarusuraisin, & Kittirattanapaiboon, 2001), consistent with the lower prevalence of subsequent hospitalization in these groups. Likewise, although more sparsely documented in the literature, cannabis dependence has been reported to cause a number of withdrawal symptoms, although generally not severe (Chauchard, Goncharov, & Krupitsky, 2014), also reducing the likelihood of in-patient episodes with only the purpose of detoxification from this drug.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, 2 studies did not have any analyzable data during the original meta-analysis' writing. 26,27 Since the publication of the original meta-analysis, we have been able to obtain data from these 2 studies, which we have included in the updated meta-analysis. Furthermore, of the original 47 studies, 2 reported on both lifetime and past-year prevalence, 28,29 so they were not included in the original meta-analysis' overall prevalence estimate to avoid publication bias from having the same sample represented twice.…”
Section: Sources Of Datamentioning
confidence: 99%